Parental Hopes and Understandings of the Value of Prenatal Diagnostic Genomic Sequencing: A Qualitative Analysis - Outram, Simon M.; Brown, Julia E. H.; Zamora, Astrid N.; Sahin-Hodoglugil, Nuriye; Ackerman, Sara L. (Frontiers in Genetics, 2022)
Objective: To provide qualitative empirical data on parental expectations of diagnostic prenatal genomic sequencing and the value of the results to families. Methods: We interviewed 15 families – mothers and/or fathers – who had had prenatal genomic sequencing about their expectations and their respective evaluations of the benefits of genomic sequencing. Results: Families’ hopes for genetic sequencing clustered around three themes: hoping to identify the cause of the fetal anomaly in a terminated pregnancy; hopes for guidance as to the likely outcome of current pregnancy; and hopes for information to support future family planning. In addition, hopes were discussed in terms of the potential for results to be beneficial in acquiring greater knowledge, while at the same time recognizing that new knowledge may raise more questions. Assessment of the value of sequencing largely mirrored these expectations when positive results seen. Negative results can also be seen as valuable in ruling out a genetic cause and in providing certainty that families had done everything that they could to know about the cause of fetal demise. Conclusion: It would appear that with guidance from genetic counsellors, families were largely able to navigate the many uncertainties of prenatal genomic sequencing and thus see themselves as benefitting from sequencing. However, support structures are essential to guide them through their expectations and interpretations of results to minimize possible harms. Engaging in the process of genomic sequencing was seen as beneficial in of itself to families who would otherwise be left without any options to seek diagnostic answers.